Approche énonciative du poème Réponse à un acte d’accusation de Victor Hugo - Loukou Fulbert Koffi (Multilinguales)
Poem « Réponse à un acted’accusation » of Victor Hugo obeys to a specific enunciation mode. It is assumed by a single speaker who convenes many other enunciators, making his speech like an antagonistic dialogue. As we will try to show it, this approach, which follows from dialogism and modalization, allows the speaker to update previous voices and to establish with them an interlocution relationship shifted in space and time.